2000
DOI: 10.1093/jexbot/51.345.769
|View full text |Cite
|
Sign up to set email alerts
|

Fluid ionic composition influences hydraulic conductance of xylem conduits

Abstract: The direct effect of fluid composition on xylem hydraulic conductance is investigated in excised stem segments of chrysanthemum (Dendranthema x grandiflorum Tzvelev cv. Cassa) plants. Dynamic changes in hydraulic conductance are accurately measured at 30 s intervals before and after modifications of the composition of the standard fluid (deionized water). It is investigated whether osmotic properties of the flowing solution influence overall hydraulic conductance by affecting the hydraulic conductance of vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(51 citation statements)
references
References 21 publications
4
45
2
Order By: Relevance
“…The finding that ions in the water promote the flow rate in stem segments was corroborated by van Ieperen et al (2000), Zwieniecki et al (2001), and several others (for example, see López-Portillo et al, 2005;Domec et al, 2007;Gascó et al, 2007;Nardini et al, 2007b).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The finding that ions in the water promote the flow rate in stem segments was corroborated by van Ieperen et al (2000), Zwieniecki et al (2001), and several others (for example, see López-Portillo et al, 2005;Domec et al, 2007;Gascó et al, 2007;Nardini et al, 2007b).…”
supporting
confidence: 54%
“…The inclusion of monovalent or divalent cations in the distilled water used to perfuse the segments immediately increased the rate of water flow, the anions being of no importance. Sugars were also without effect (van Ieperen et al, 2000;van Ieperen and van Gelder, 2006). Zwieniecki et al (2001) found the same in stem segments of Laurus nobilis and Fraxinus americana.…”
Section: Data On Stem Perfusion and The Pit Membrane Pectin-swelling mentioning
confidence: 77%
“…Recent work suggests that changes in pit membrane porosity with ionic strength of the xylem sap are responsible for changes in overall xylem conductivity (Zimmermann, 1983;Van Ieperen et al, 2000;Zwieniecki et al, 2001a). However, this can only be possible if vessels are shorter than their saturating lengths.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, published results [144,156], have shown an effect of ionic composition on hydraulic conductance. This effect seems to be small (10%) in most of the experimented plants species and dose-dependent, but it can be significant in other plants, depending on the ion concentration, pH, and non-polar solvent.…”
Section: Quantitative Characteristics Of Hydraulic Architecturementioning
confidence: 99%